Penerjemahan Drama Bila Malam Bertambah Malam Karya Putu Wijaya: Sebuah Kajian Penerjemahan Teatrikal - Prihantono, Kahar Dwi (Jurnal Penerjemahan, 2016)
Applied translation studies provide a wider room for collaborations between translation study and other disciplines. The collaboration of translation study with literature study, especially theatrology, result in the theatrical translation study as a branch of applied translation studies. This paper examines the theatrical translation of Putu Wijaya’s Bila Malam Bertambah Malam (BMBM) as translated into Javanese by Aslam Kussatyo. Galur (GLR), the theatrical translation of BMBM, serves as the object of this study. By applying the theatrical translation strategy, introduced by Susan Bassnett (1991) and covering cuts, adding, and adding with modifications, the writer tries to reveal translation strategies in the translation. The results of the study prove that--during the first phase of translation-- the translator applied a new strategy of theatrical translation (never before exposed by Bassnett) namely cuts with modifications. This strategy is traceable through the analyses of acculturation, gestic text, playtext, and speakability dimensions. While in the second stage of translation, the translators (director and stage crews) applied the strategy of adding with modifications in terms of performability and subtext dimensions. Key words: theatrical translation, strategy, cuts, adding